Understanding the Potential In Vitro Modes of Action of Bis(β‐diketonato) Oxovanadium(IV) Complexes. (26th May 2021) - Sergi, Baris; Bulut, Ipek; Xia, Ying; Waller, Zoë A. E.; Yildizhan, Yasemin; Acilan, Ceyda; Lord, Rianne M.
Abstract: To understand the potential in vitro modes of action of bis(β‐diketonato) oxovanadium(IV) complexes, nine compounds of varying functionality have been screened using a range of biological techniques. The antiproliferative activity against a range of cancerous and normal cell lines has been determined, and show these complexes are particularly sensitive against the lung carcinoma cell line, A549. Annexin V (apoptosis) and Caspase‐3/7 assays were studied to confirm these complexes induce programmed cell death. While gel electrophoresis was used to determine DNA cleavage activity and production of reactive oxygen species (ROS), the Comet assay was used to determine induced genomic DNA damage. Additionally, Förster resonance energy transfer (FRET)‐based DNA melting and fluorescent intercalation displacement assays have been used to determine the interaction of the complexes with double strand (DS) DNA and to establish preferential DNA base‐pair binding (AT versus GC). Abstract : Outstanding oxovanadium ! Functionalized bis(β‐diketonato) oxovanadium(IV) complexes exhibiting increased cytotoxicity towards lung cancer cells are reported. The compounds show interactions with genomic DNA, a preference for A‐T binding and high levels of DNA fragmentation. Importantly, they generate high levels of reactive oxygen species and undergo apoptosis, which is predicted to be the main mode of cell death.